Seasonal Prevalence Pattern Of Diseases Of Ruminants In Rural Kamrup District Of Assam - Dutta, P.R.; Hafiz, A.; Bora, Sarbani; Phukan, A.; Kalita , D.N. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Knowledge of various disease incidences of animals of a particular geographical area along with their seasonal prevalence pattern helps the field Veterinarians in quick and accurate diagnosis. It also helps to take up required prevention and control strategies. In the present study, clinical cases of ruminants recorded in the four veterinary dispensaries of Kamrup rural district for two consecutive years were collected and analysed to find out the prevalence pattern of different diseases.